Potensi Ekstrak Daun gambir (Uncaria gambir Roxb) sebagai Pestisida Nabati untuk Mengendalikan Hama Ulat Api (Sethotosea asigna van Eecke) - Dibisono, Mhd Yusuf; Ginting, Makhrani Sari; Hariri, Syauqi (JURNAL AGROPLASMA, 2022)
Gambir (Uncaria gambir) is a herbaceous plant that has alkaloid level sin the form of chemicall compounds suchas catechins, tannin catecu (tannin/tannat), querchitin, flouresin, and several other compounds. The aim of this study is to deterine the effectiveness of the concentration of gambir leaf extract (U. gambir Roxb), against theÂ  mortality of fire caterpillarpest (S.asigna). Research was arrenged in anonfactorial Randomized Block Design (RBD) with 5 treatments, namely U0: No Application (Control), U1: Application with 8% gambier leaf extract, U2: Application with 16% gambier leaf extract, U3: Application with 24% gambier leaf extract and U4: Application with 32% gambier leaf extract. The results showed that effective application of gambier leaf extract was at concentration of 32% where at 5 days after the application the mortality rate offire caterpillar had reached 100% and suppressed the intensity of leaf attacks by14.28%.Â Keywords: Botanical Pesticide, Uncaria gambir extract, Setothosea asigna.